Darkening of lead‐ and iron‐based pigments on late Gothic Italian wall paintings: Energy dispersive X‐ray fluorescence, μ‐Raman, and powder X‐ray diffraction analyses for diagnosis: Presence of β‐PbO2 (plattnerite) and α‐PbO2 (scrutinyite). (23rd January 2020) - Costantini, Ilaria; Lottici, Pier Paolo; Bersani, Danilo; Pontiroli, Daniele; Casoli, Antonella; Castro, Kepa; Madariaga, Juan Manuel
Abstract: This work reports the results of an extensive study carried out on the wall paintings preserved inside the Saint Stephen's chapel in Montani (Val Venosta, Bozen, Italy), by means of μ‐Raman spectroscopy, portable X‐ray fluorescence (XRF) spectrometry, and powder X‐ray diffraction, in order to characterize materials and their alteration products that cause the blackening of paintings. In situ XRF analysis allowed identifying the areas of interest where the blackening appeared. The complementary analytical techniques allowed reconstructing a chromatic palette used by the artists that includes expensive pigments, such as lapis lazuli and cinnabar, indicating a wealthy client. Raman spectra at very low power recorded on blackened degraded samples showed the presence of a mixture of the two polymorphs of lead (IV) dioxide, plattnerite (β‐PbO2 ), and scrutinyte (α‐PbO2 ), as degradation products of lead‐based pigments. On these samples, no evidence of white lead was found, although a white lead conversion treatment had been applied on the paintings. The degradation of red lead (Pb3 O4 ) into a mixture of plattnerite, scrutinyte, and anglesite (PbSO4 ) was demonstrated in some darkened samples. Furthermore, the degradation of haematite (Fe2 O3 ) with the formation of magnetite (Fe3 O4 ) and coquimbite (Fe2 (SO4 )3 ·9H2 O) was also identified as responsible for the blackening of the paintings. The influence of original materials and environmental and anthropogenic factors such as the valley's orography and the presence of contaminating agents (SOx ) is discussed to explain the decay phenomena. Abstract : The wall paintings preserved inside the Saint Stephen's chapel in Montani (Bozen, Italy) were analysed in order to characterize materials and their alteration products that cause the blackening of paintings. Raman spectra showed the presence of a mixture of plattnerite (β‐PbO2 ) and scrutinyte (α‐PbO2 ), as degradation products of lead‐based pigments. The degradation of haematite (Fe2 O3 ) with the formation of magnetite (Fe3 O4 ) and coquimbite (Fe2 (SO4 )3 ·9H2 O) was also identified as responsible for the blackening of the paintings.